Proceedings of the 5th International Conference on the Durability of Concrete Structures 2016
DOI: 10.5703/1288284316140
|View full text |Cite
|
Sign up to set email alerts
|

Designing Repeatable Self-Healing into Cementitious Materials

Abstract: Designing self-healing into cementitious materials can open a new world of opportunities for resilient concrete infrastructure under service loading conditions. The self-healing process should be robust as well as repeatable, allowing for self-repair after multiple damage events. The repeatability poses great challenges when self-healing strategies mainly rely on the formation of low-strength calcium carbonate healing product, complicated by the localized cracking behavior of cementitious materials. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Subsequently, the next step would be to analyze if the sealing mechanism is maintained over time after several cracking-healing cycles (self-healing repeatability). Compared to the large number of investigations on self-healing [6,7,10,11,18,19,20,9] among others, studies on the persistence of the healing capacity under repeated cracking and healing events of self-healing FRCC are less numerous [22,[39][40][41][42] which has motivated this research. Among the cited studies on the persistence of the healing capacity under repeated cracking events, it is worth recalling the works by Snoeck et al [22] and Sahmaran et al [39].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the next step would be to analyze if the sealing mechanism is maintained over time after several cracking-healing cycles (self-healing repeatability). Compared to the large number of investigations on self-healing [6,7,10,11,18,19,20,9] among others, studies on the persistence of the healing capacity under repeated cracking and healing events of self-healing FRCC are less numerous [22,[39][40][41][42] which has motivated this research. Among the cited studies on the persistence of the healing capacity under repeated cracking events, it is worth recalling the works by Snoeck et al [22] and Sahmaran et al [39].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, pre‐cracking is a force/displacement‐controlled test in which the specimen is cracked up to a specific percentage of its ultimate force/displacement capacity. After testing six dummy specimens under four‐point bending test, it was observed that the continuation of postlinear behavior (deflection‐hardening stage) is highly dependent on the weak point of cracking, crack propagation pattern and the fiber orientation and dispersion at the crack locations 24,35 . Therefore, in this study the specimens were precracked up to a point where a visually distinguishable crack (which was measured by DIC to be between 200 and250 μm, after unloading) was observed on the specimens.…”
Section: Experimental Programmentioning
confidence: 92%
“…Using precracking results of ECC prisms to determine the compression cycle load limit hardening stage) is highly dependent on the weak point of cracking, crack propagation pattern and the fiber orientation and dispersion at the crack locations. 24,35 Therefore, in this study the specimens were precracked up to a point where a visually distinguishable crack (which was measured by DIC to be between 200 and250 μm, after unloading) was observed on the specimens. This high deflection was selected purposefully so that fibers between cracks will not be able to interfere with the UPV measurements.…”
Section: Test Plan and Exposure Conditionsmentioning
confidence: 99%
See 2 more Smart Citations